Response and Defence Mechanisms of Vegetable Crops against Drought, Heat and Salinity Stress - Giordano, Maria; Petropoulos, Spyridon A.; Rouphael, Youssef (Agriculture (Basel), 2021)
Environmental pollution, increasing CO2 atmospheric levels and the greenhouse effect are closely associated with the ongoing climate change and the extreme climatic events we are witnessing all over the Earth. Drought, high temperature and salinity are among the main environmental stresses that negatively affect the yield of numerous crops, challenging the world food safety. These effects are more profound in vegetable crops which are generally more susceptible to climate change than field or tree crops. The response to single or combined environmental stressors involves various changes in plant morphology and physiology or in molecular processes. Knowing the mechanisms behind these responses may help towards the creation of more tolerant genotypes in the long-term. However, the imediacy of the problem requires urgently short-term measures such as the use of eco-sustainable agricultural practices which can alleviate the negative effects of environmental pollution and allow vegetable crops to adapt to adverse climatic conditions. In this review, the main abiotic stressors were examined, namely drought, heat and salinity stress, focusing on the mechanisms involved in the most common vegetable crops responses. Moreover, the use of eco-sustainable cultural techniques, such as biostimulants, grafting and genomic sequencing techniques, to increase the quality of tomato crop under adverse environmental conditions are also presented.